Closing the Gender Gap in Leadership Positions: Can Expanding the Pipeline Increase Parity? - Ryan Brown; Hani Mansour; Stephen D. O'Connell (Institute of Labor Economics (IZA), 2018)
Gender gaps in leadership roles may be reduced by increasing the number of women in career stages that typically precede high-status positions. This can occur by increasing the supply of experienced women, inspiring new female candidates for these positions, and/or changing beliefs about women as leaders. In this study, we investigate whether and how adding women to a career pipeline can reduce gender gaps in higher-ranking positions over time. Specifically, we examine the effects of women's local electoral success on subsequent female candidacy at higher levels of government in India from 1977 to 2014. We use close elections won by women contesting state legislature seats to identify the effect of pipeline expansion on later candidacy for the national parliament. The results indicate that for each additional lower-level seat won by a woman, there is a 30 percent increase in the number of female candidates in subsequent national legislature elections. This effect is driven by new candidates and not by career politicians, and women receive a disproportionately favorable increase in the vote share. These effects are strongest in areas with low levels of existing female political participation and empowerment. The findings are consistent with a mechanism in which exposure reduces bias, allowing for updated beliefs about the viability of latent candidates who then run for higher office.
Keywords: J16; J71; P16; 330; gender gap; political candidacy; female politicians; India